POTANSİYEL OLARAK KÜRATİF REZEKSİYON GEÇİREN MİDE KANSERİ HASTALARINDA MİKROSKOPİK REZEKSİYON SINIRI TUTULMASININ ERKEN VE GEÇ SONUÇLARI - ERSAN, Yılmaz; YAVUZ, Nihat; KUŞASLAN, Ramazan; ŞENOCAK, Mustafa; Doğusoy, Gülen; ÇİÇEK, Yusuf and ERGÜNEY, Sabri (Cerrahpaşa Medical Journal, 2019)
Background and Design.- At a curative resectional procedure in for cases of gastric cancer, a matter of great import is boundaries of the invading process extending to the oral and/or anal directions. Failure to appreciate this fact during gastrectomy leads to transection in an area invaded by the tumor. Resection-line involvement has been shown to have a causing effect on both anastomatic leakage and perioperative mortality. It also predisposes to anastomotic recurrence and long-term survival rate is impaired. Prognostic impact of resection-line involvement was investigated in patients undergoing potentially curative gastrectomy. Information collected from medical and pathological records included the age and gender of patients, location of tumor, histology type histologic grade, macroscopic type, regional lymph node metastasis and residual tumor in resectional lines. A positive margin was defined as disease present at the line of luminal transection in the mucosa, submucosa and/or serosa. Results.- Resection-line involvements were seen in 30 (16%) of the 185 evaluable patients, Resection-line involvement was associated with age (p=0.08), tumor location (p=0.007), tumor differentiation (p=0.01), macroscopic type of tumor (p=0.19), nodal staging (p=0.002) number of the metastatic nodes (p=0.003) and type of operation (p=0.08). The presence of positive margins was a significant and independent factor of outcome for the entire group (n=185) and associated with worse survival (p=0.016). The significance of a positive microscopic margin in gastric cancer was dependent on the extent of disease. This factor was not predictive of outcome in patients who had undergone complete gross resection and have pathologically proved advanced disease. However, if both groups of patients are stratified according to stage, differentiation, macroscopic type of the tumor, and lymph node metastases, resection-line involvement determined a shorter survival only in patients with stage-II, welldifferentiated, ulceroinfiltrative carcinoma and no stage. Conclusion.- In gastric cancer patients, undergoing potentially curative resections, a more aggressive assessment of resection lines is mandatory. Our date suggest, in the cases of positive margins that re-excision of resection line/lines should be considered ed only for patients with stage-II, well-differentiated, ulceroinfiltrative carcinoma and No stage disease while patients with advanced disease should be watched closely without the need for a more aggressive surgical approach.